Co-Authors of Article - Perspective Varieties of Red Cabbage for Repeated Culture in Uzbekistan - Makhsud Adilov; Bekhzod Rustamov; Makhfurat Amanova; Abdumalik Rustamov (Central Asian Journal of Theoretical and Applied Science, 2022)
Perspective varieties of red cabbage for repeated culture in Uzbekistan. The article presents the results of a study of a collection of 24 samples (2015), preliminary variety testing of 8 samples (2016-2017) and competitive variety testing of 5 samples (2018-2019). In variety tests, it was found that all tested variety samples belong to the most precocious is Omero F1, the least precocious of the Red Dinasty F1. For re-culture, a Ranchero F.